Multicopter Flight Controller - Suhaimi, Muhammad Firdaus; Zahar, Mohd Muzaffar; mix mojingkui, jwellbe; Asmat, Muhammad Asyraf (Multidisciplinary Applied Research and Innovation, 2022)
A drone is an Unmanned Aerial Vehicle (UAV). It can also be said to be an unmanned aircraft. The drone is operated using a human controlled remote control. Essentially, a drone is a flying robot that can be remotely controlled or fly autonomously through software-controlled flight plans in their embedded systems, working in conjunction with onboard sensors and GPS. For this project, we plan to create a drone known as Multi-copter Flight Controller. The main challenge is to precise the positioning and the PID control of the drone by using Arduino uno.  The purpose of this project is to develop a drone based on Arduino Uno. In addition, by doing this project, we can learn how to apply our knowledge during our diploma in electrical engineering studies. To complete this project, we need to know the hardware, software, and circuit design of the drone. The main material in this project is Arduino uno, triple-axis gyro, electronic speed controller (ESC), motors, transmitter, and receiver. The significant of this project is to create and provide knowledge and data how to create multi-copter drone based on Arduino uno.